2020
DOI: 10.21203/rs.3.rs-17663/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors of the suprasternal lymph node metastasis in papillary thyroid carcinoma with clinical lateral cervical lymph node metastasis

Abstract: Background: Metastatic lymph nodes are occasionally found in the suprasternal lymph nodes in patients with papillary thyroid cancer (PTC), but there are few studies on these lymph nodes. Therefore, we investigated the frequency and risk factors of suprasternal lymph node metastasis in PTC patients with lateral cervical lymph node metastasis.Methods: A total of 85 patients with cN1b PTC underwent total thyroidectomy with elective lateral neck dissection including the suprasternal lymph nodes. We analyzed the co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, previous studies recommended dissecting the LNSS and SSLN in PTC patients with lateral compartment lymph node metastasis. 11,12,15,16 In addition, previous studies supported LNSS and SSLN dissection because it is a low risk and easy procedure.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, previous studies recommended dissecting the LNSS and SSLN in PTC patients with lateral compartment lymph node metastasis. 11,12,15,16 In addition, previous studies supported LNSS and SSLN dissection because it is a low risk and easy procedure.…”
Section: Resultsmentioning
confidence: 96%
“…12 Recently, Kwon et al reported the rate of suprasternal lymph node metastasis in PTC patients who underwent therapeutic lateral neck dissection due to clinically positive nodes in the lateral compartment as 12.9%. 16 They reported that SSLN metastasis was associated with tumors located in the inferior pole of the thyroid gland and level IV metastasis. 16 In addition, Yuan et al suggested a group of lymph nodes between the investing layer of the deep cervical fascia and the infrahyoid strap muscle fascia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Papillary thyroid cancer (PTC) is an endocrine malignancy that occurs in thyroid follicular cells [1]. The incidence of PTC has increased rapidly worldwide over the last 3 decades.…”
Section: Introductionmentioning
confidence: 99%